Dostoevsky's legal and moral philosophy : the trial of Dmitri Karamazov - Belliotti, Raymond A., 1948- (Value Inquiry Book Series, 2016)
This work closely examines the trial of Dmitri Karamazov as the springboard to explaining and critically assessing Dostoevsky's legal and moral philosophy. The author connects Dostoevsky's objections to Russia's acceptance of western juridical notions such as the rule of law and an adversary system of adjudication with his views on fundamental human nature, the principle of universal responsibility, and his invocation of unconditional love. Central to Dostoevsky's vision is his understanding of the relationship between the dual human yearnings for individualism and community. In the process, the author related Dostoevsky's conclusions to the thought of Plato, Augustine, Anselm, Dante, Kierkegaard, Schopenhauer, Nietzsche, and Sartre. Throughout the work, the author compares, contrasts, and evaluates Dostoevsky's analyses with contemporary discussions of the rule of law, the adversary system, and the relationship between individualism and communitarianism.